Knowledge, attitude and practices about exclusive breastfeeding among antenatal women - Vaidya, Annal A.; Warke, Himangi S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Breastmilk is considered as one of the healthiest, nutrition-rich yet least expensive method of infant feeding. It is a universally accepted fact that breastmilk meets all the nutritional demands of the new-born. There are extensive benefits of breastfeeding for the new-born as well as for the nursing mother which have been documented from time to time. Methods: A multiple-choice questionnaire was used to interview the participants during data collection. Results: Using the IBM SPSS version 20 software, descriptive analysis of the categorical variables has been presented using frequency and percentage tables. Regarding the practices about breast feeding in primigravidas, their concepts about the same have been captured in this study. Conclusions: Though the knowledge about exclusive breast feeding was not extraordinary among the participants, they had a very favourable attitude towards the same. Almost all patients were also extremely receptive and inquisitive during the session for discussion about the same.